Dengue vector control: assessing what works? - Horstick, Olaf; Boyce, Ross; Runge-Ranzinger, Silvia (The Southeast Asian journal of tropical medicine and public health, 2017)
Primary prevention of dengue remains difficult, and continues to be difficult, relying mostly on vector control, with historical success, but lately there is also a partially effective vaccine. Vector control may continue to play a role, with the most efficacious and effective vector control methods. To establish this, high level evidence such as systematic reviews have been developed for applied vector cotrol methods, but also on service delivery. The systematic reviews followed the PRISMA statement. For single vector control interventions work has been undertaken on peridomestic space spraying, Temephos, Bacillus thuringiensis israelensis, Copepods and larvivorous fish. Further work is currently published on pyriproxifen and indoor residual house spraying (IRS). For a particular service delivery, there is existing work on outbreak response and on vector control service delivery. Nearly all vector control methods showed excellent results in at least one study, either on larvae, or adults, or even perhaps on dengue transmission: 1) Vector control can be effective, implementation remains an issue, including delivery structures, 2) Single interventions are probably not useful, efficacy varies, with little sustainability, 3) Combinations of interventions have mixed results, 4) Interventions are often applied in outbreaks (compared to routine vector control), effectiveness is also questionable, 5) Key elements for more effective vector control measures may be timely alerts of outbreaks, followed by immediate vector control measures, including health promotional campaigns, 6) Careful implementation may be most important.
DOI nicht vorhanden
Gesehen am 05.09.2018